Simulated radiographic bone and joint modeling from 3D ankle MRI: feasibility and comparison with radiographs and 2D MRI. - Nordeck, Shaun; Koerper, Conrad; Adler, Aaron; Malhotra, Vidur; Xi, Yin; Liu, George; Chhabra, Avneesh; Nordeck, Shaun M; Koerper, Conrad E; Liu, George T (Skeletal Radiology, 2017)
Purpose: The purpose of this work is to simulate radiographs from isotropic 3D MRI data, compare relationship of angle and joint space measurements on simulated radiographs with corresponding 2D MRIs and real radiographs (XR), and compare measurement times among the three modalities.Materials and Methods: Twenty-four consecutive ankles were included, eight males and 16 females, with a mean age of 46 years. Segmented joint models simulating radiographs were created from 3D MRI data sets. Three readers independently performed blinded angle and joint space measurements on the models, corresponding 2D MRIs, and XRs at two time points. Linear mixed models and the intraclass correlation coefficient (ICC) was ascertained, with p values less than 0.05 considered significant.Results: Simulated radiograph models were successfully created in all cases. Good agreement (ICC > 0.65) was noted among all readers across all modalities and among most measurements. Absolute measurement values differed between modalities. Measurement time was significantly greater (p < 0.05) on 2D versus simulated radiographs for most measurements and on XR versus simulated radiographs (p < 0.05) for nearly half the measurements.Conclusions: Simulated radiographs can be successfully generated from 3D MRI data; however, measurements differ. Good inter-reader and moderate-to-good intra-reader reliability was observed and measurements obtained on simulated radiograph models took significantly less time compared to measurements with 2D and generally less time than XR.